Italian translation, cultural adaptation and validation of the “American Orthopaedic Foot and Ankle Society’s (AOFAS) ankle-hindfoot scale” - Leigheb, Massimiliano; Janicka, Paulina; Andorno, Silvano; Marcuzzi, Augusto; Magnani, Corrado; Grassi, Federico (Acta Biomedica Atenei Parmensis, 2016)
Background and Aim of the work Ankle and hindfoot injuries are common and may lead to functional impairment, disability, exclusion from occupational and daily activities. It’s necessary a standardized method for assessing treatment outcomes in people with same condition and disease. American-Orthopaedics-Foot-and-Ankle-Society’s-Ankle-Hindfoot-Evaluation-Scale (AOFAS-AHES) is specific to estimate clinical problems of the ankle-hindfoot. Outcome evaluation scales should be translated and culturally adapted into the language of the investigated patient. Our purpose was to translate and culturally adapt into Italian AOFAS-AHES, and to check its reproducibility and validity. Methods An Italian translation of the AOFAS-scale was retranslated into English by a native English and compared to the original to define a second correct Italian-version, that was submitted to 50 randomized patients operated at their ankle or hindfoot with a minimum follow-up of 6 months for cultural adaptation, and to 10 healthcare professionals to check comprehension of the medical part. To check intra and inter-observer reproducibility each patient underwent 2 interviews by interviewer-A and 1 by B. ShortForm(SF)-36-questionnaire for quality of life and Visual-Analogue-Scale (VAS) for pain were also compared for validation. The Pearson’s-Correlation-Coefficient and the Intra-Class-Correlation coefficient were calculated to check inter and intra-observer reproducibility for validation. Results Cultural adaptation revealed to be good. We obtained a good correlation of the inter and intra-observer reproducibility. Further validation of the Italian-AOFAS-AHES was obtained comparing AOFAS results to SF-36. Conclusions Italian translation, cultural adaptation and validation of the AOFAS-AHES has been performed successfully and could be useful to improve assistance quality in care practice.